1985
DOI: 10.1079/bjn19850113
|View full text |Cite
|
Sign up to set email alerts
|

The development of acid and pepsin (EC 3. 4. 23. 1) secretory capacity in the pig; the effects of age and weaning

Abstract: 1. The development of gastric secretory capacity of hydrochloric acid and pepsin (EC 3. 4. 23. 1) was studied in thirty-eight Large White x Landrace pigs from the litters of six sows (three pairs of two), 9–38 d of age. The pigs of each pair of sows were born within 24 h of each other. The pigs of a litter were paired according to sex and size and cross-fostered, i.e. one pig from each pair was allocated to each sow.2. One litter from each pair was reared entirely by the sow (milk-fed, MF) whereas the other li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
4

Year Published

1988
1988
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 48 publications
0
30
0
4
Order By: Relevance
“…In suckling pigs, the maximal acid output per unit weight remains quite constant (Cranwell, 1985). Stomach content acidification is mainly due to the presence of lactic acid, resulting from bacterial fermentation of lactose (Cranwell et al, 1976).…”
Section: Stomachmentioning
confidence: 99%
“…In suckling pigs, the maximal acid output per unit weight remains quite constant (Cranwell, 1985). Stomach content acidification is mainly due to the presence of lactic acid, resulting from bacterial fermentation of lactose (Cranwell et al, 1976).…”
Section: Stomachmentioning
confidence: 99%
“…It is thought that creep feeding predisposes suckling pigs to subsequent stressful weaning through prompting gut adaptations to solid feed. Several studies have confirmed that the provision of solid diets containing complex carbohydrates to suckling pigs stimulates acid and pepsin secretion in the stomach (Cranwell, 1977(Cranwell, , 1985Cranwell and Stuart, 1984) and enhances the activity of some stomach and pancreatic enzymes (Corring et al, 1978;Corring, 1980;de Passillle et al, 1989). Pierzynowski et al (1990) suggested that changes in pancreatic output of protein and enzymes around weaning were developmental adaptations of the gut to the digestion of the diets, and were more related to the dietary changes rather than the weaning age or weaning per se.…”
Section: Creep Feeding Weaning Age and Mixing Of Different Litters mentioning
confidence: 99%
“…La flora microbiana natural del tracto digestivo proporciona las condiciones necesarias para el eficiente uso de los nutrientes recibidos con los alimentos (Cranwell, 1985;Rosmini et al, 2004). Para este fin, estas bacterias utilizan diferentes mecanismos de acción relacionados con el bienestar del animal (Castillo y Alves da Trindade, 2007;Champagne et al, 2005;De Lange et al, 2010y Blajman et al, 2015.…”
Section: Resultados Y Discusiónunclassified